الخطاب الصوفي وأثره في تنمية القيم الروحية - مسعي, محمد السعيد; حناي, محمد (جامعة الوادي - University of Eloued, 2021)
يتناول هذه المقال الخطاب الصُّوفي، ويُعالج مضامينه في تنمية القيم الرُّوحيَّة مُبرزاً أهمية هذا الخطاب في ظلِّ التَّحديات المعاصرة، ومُستعرضاً أبعاده المتعدِّدة في تنمية القيم الرُّوحيَّة لإنسان العصر المعاصر الذي تحيط به الملذات من كلِّ الاتجاهات وتتقاذفه الأهواء وغطرسة الأنا في كلِّ الأزمنة واللحظات، مستنداً في ذلك إلى بعض خطابات مشايخ الطُّرق الصُّوفية في عصرنا المعاصر؛ كما يهدف هذا المقال إلى توضيح قيمة هذا الخطاب في تعزيز قيم التَّفاعل الإيجابي مع روح العصر وتنمية الحركة العلمية والثقافية التي هي أساس البناء المجتمعي للقيام بإحداث نهضة علمية والرقي بالفكر إلى المستوى المطلوب. This article deals with the Sufi discourse, addresses its contents in the development of spiritual values, underscores the importance of discourse in the face of contemporary challenges and reviews its multiple dimensions in the development of the spiritual values of the people of the contemporary age who it is surrounded by pleasures of all directions and is surrounded by the desire and the hubris of Alana At all times and moments, passions and the arrogance of the ego confront him in all times and moments, relying on some a speech of Sufi Sheikhs in our contemporary era. This article also aims to clarify the importance of this speech in promote positive interaction values with the spirit of the era times, And the development of the scientific and cultural movement, which is the basis of community-based construction to do so To bring about a scientific renaissance and to bring thought to the required level.
Sufi discourse and its impact on the development of spiritual values
مقال
Keywords: الخطاب الصُّوفي ، القيم الرُّوحيَّة، التَّحديات المعاصرة ، التَّفاعل ، أثر الإيجابي; The Sufi discourse , The spiritual values, The Contemporary challenges, The interaction , Effect The positive.